Absence of costal element of the foramen transversarium of atlas vertebrae - Chauhan, Renu; Khanna, Jugesh (International Journal of Research in Medical Sciences, 2017)
Background: Since scanty literature is available on the absence of costal element forming foramen transversarium of atlas vertebra therefore this study was undertaken. Atlas vertebrae were examined to see the presence of foramen transversarium and their boundaries. Methods: Hundred foramina transversaria of 50 atlas vertebrae were examined grossly. Results: Foramen transversarium was seen to be present in all the transverse processes of the atlas vertebrae examined. Costal element was found to be missing in seven foramina tranversaria out of 100 foramina seen. It was found to be absent on the right side in three vertebrae and in two it was absent bilaterally. Conclusions: In case the costal element of the foramen transversarium is absent, the second part of vertebral artery passing through this foramen is liable to be damaged while operating at the level of atlanto-occipital joint the operating surgeon should be aware of such variations so as to avoid injury of second part of vertebral artery and subsequently preventing any kind of neurological involvement. Radiologists must also know about such variations so as to correctly interpret radiological image of the craniovertebral region.